Pengaruh Green Accounting dan Corporate Social Responsibility Terhadap Profitabilitas Sub Sektor Logam Periode 2020-2023 pada Bursa Efek Indonesia - Andina Yulianti; Leriza Desitama Anggraini; RM. Rum Hendarmin (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to examine the influence of Green Accounting and Corporate Social Responsibility (CSR) on profitability in the metals sub-sector for the 2020-2023 period on the Indonesia Stock Exchange. The secondary data used comes from the annual financial reports of companies listed on the Indonesia Stock Exchange. The analytical method used is regression to test the relationship between Green Accounting, CSR and company profitability. The results of the analysis show that Green Accounting has a significant positive influence on the profitability of metal companies with a t value of 5.324 and a significance level (sig) of 0.000 < 0.05. This shows that the implementation of Green Accounting contributes positively to the company's financial performance. Apart from that, Corporate Social Responsibility also has a significant influence on profitability with a t value of 3.542 and a significance level (sig) of 0.000 < 0.05, confirming that effective CSR practices also have a positive impact on the profitability of metal companies. In conclusion, both Green Accounting and CSR has an important role in increasing company profitability in the metal sub-sector in Indonesia. The implications of this research underscore the importance of integrating sustainable practices in a company's business strategy to achieve long-term financial goals and meet stakeholder expectations regarding social and environmental aspects.